A Multi-modal Transportation Score to Evaluate Infrastructure Supply-demand for Commuters. (2016) - Chandra, Shailesh; Braughton, Malcolm; Galicia, Luis David; Sanchez, Alfredo; Medina, Michael; Aldrete, Rafael
Abstract: This research presents a novel multi-modal transportation score for commuters bicycling or walking to transit stops. The score requires basic data necessary for its calculation, namely - travel time information, population, employment and the transportation network for the considered modes within the multi-modal context. The proposed score is validated with observations from data obtained for El Paso, Texas. A sensitivity analysis was carried out on transportation supply and demand assessment of multi-modal transportation system for El Paso and its surrounding rural cities of Socorro, San Elizario, Horizon City, Vinton and Anthony. Results showed that the supply (multi-modal transportation facility) for commuters do not meet the needs of the latent demand (population or employment) for most areas in El Paso and for all the five rural cities studied. The disparity between supply-demand is mainly attributed to the poor last mile transport connectivity available to bicyclists and pedestrians around transit stops.